Economic Report on Africa 2007 - United Nations (United Nations, 2008)
Profound changes are increasingly occurring in all areas of the world economy. While the industrialized and emerging economies are able to contain the multiple external and internal shocks generated by these changes, Africa on its part is still struggling to cope with them. The analyses reported in the present edition of the Report review the world economy and map out prospects for development in Africa through the institution of structural reforms to diversify and modernize the economy, enhance competitiveness, promote trade, accelerate growth and reduce poverty.